Łagodne zaburzenia poznawcze – aktualny problem geriatryczny = Mild cognitive impairment – current geriatric issue - Beck, Oliwia; Łakomski, Mateusz; Kędziora–Kornatowska, Kornelia; Waśniowski, Wojciech; Radzimińska, Agnieszka; Weber-Rajek, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Beck Oliwia, Łakomski Mateusz, Kędziora–Kornatowska Kornelia, Waśniowski Wojciech, Radzimińska Agnieszka, Weber‑Rajek Magdalena, Żukow Walery. Łagodne zaburzenia poznawcze – aktualny problem geriatryczny = Mild cognitive impairment – current geriatric issue. Journal of Education, Health and Sport. 2016;6(4):515-527. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154244 http://ojs.ukw.edu.pl/index.php/johs/article/view/3859 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 28.04.2016. Łagodne zaburzenia poznawcze – aktualny problem geriatryczny Mild cognitive impairment – current geriatric issue Oliwia Beck1, Mateusz Łakomski1, Kornelia Kędziora–Kornatowska1, Wojciech Waśniowski2, Agnieszka Radzimińska3, Magdalena Weber-Rajek3, Walery Żukow4 1Katedra i Klinika Geriatrii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, UMK w Toruniu 2Pallmed Sp. z o.o., ul. W. Roentgena 3, Bydgoszcz 3Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, UMK w Toruniu 4Uniwersytet Kazimierza Wielkiego, Bydgoszcz Streszczenie Artykuł przedstawia aktualny stan wiedzy dotyczący łagodnych zaburzeń poznawczych (Mild Cognitive Impairment, MCI). Termin ten, początkowo uważany za stan przejściowy pomiędzy prawidłowym funkcjonowaniem poznawczym a objawami choroby Alzheimera (Alzheimer’s disease, AD), obecnie oznacza heterogenną grupę widocznych i obiektywnych deficytów kognitywnych u pacjentów bez rozpoznanego otępienia. Deficyty te, choć zauważalne zarówno dla osób nimi dotkniętych, jak i ich otoczenia, są na tyle nieznaczne, że nie wpływają na podstawowe czynności życia codziennego i zdolność do samodzielnej egzystencji. Rozpowszechnienie MCI szacuje się na 15 – 30% wśród osób powyżej 60 roku życia; rośnie ono wraz z wiekiem. Łagodnym zaburzeniom poznawczym – zwłaszcza ich postaci amnestycznej - przypisuje się podwyższone ryzyko rozwinięcia się otępienia, wynoszące 10 – 15% rocznie (przy 1 – 2% dla populacji ogólnej). Z tego powodu identyfikacja osób z MCI jest obecnie najważniejszą strategią opóźniania postępu otępień i zapobiegania im. Słowa kluczowe: łagodne zaburzenia poznawcze, funkcjonowanie poznawcze, wiek podeszły, otępienie Summary The article describes current state of knowledge on Mild Cognitive Impairment (MCI). The term, initially considered a transitional state between normal cognitive aging and mild Alzheimer’s disease (AD), currently covers heterogenous group of noticeable and objective cognitive deficits in patients without the diagnosis of dementia. These deficits, although apparent for both afflicted persons and their environment, do not interfere substantially with basic activities of daily living nor result in inability to live independently. The prevalence of MCI is estimated between 15 and 30% in individuals over 60 years old. Subjects with MCI constitute a high risk group because they develop dementia at a rate of 10% to 15% per year compared with 1% to 2% per year in the general population. Therefore, it is critical to identify patients with MCI in order to prevent dementia and delay its progress. Keywords: Mild Cognitive Impairment, cognitive functioning, old age, dementia